Essentials of Marketing Research, 7th Edition - Barry J. Babin (Cengage Learning, 2018)
ESSENTIALS OF MARKETING RESEARCH, provides a concise, yet complete guide to the design, execution, analysis, and reporting of marketing research to support smart business decisions. This proven resource provides valuable business context while introducing both traditional research methods, such as designing questionnaires, and the latest technological advances, including current data collection devices, basic data analysis tools, practical approaches to data analytics, and the impact of social media and artifactual online data. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.